Leadership Styles: Bibliometric Analysis of Doctorate And Master Thesis (Third Sector Social Economic Review, 2025)
Leadership has emerged as a critical factor that directly influences the success of organizations and the motivation of employees. Leadership is recognized as a key element in enhancing employee performance in business processes and achieving organizational goals. Consequently, the evolution of leadership over time and the impacts of various leadership approaches have become significant topics of study for researchers. Particularly in recent years, changes and innovations within the business world have transformed approaches to leadership, resulting in the emergence of new leadership styles.A review of academic studies over the past decade reveals frequent discussions around leadership styles such as charismatic leadership, autocratic leadership, and transformational leadership, with a noticeable increase in studies on these topics. This study aims to analyze trends in academic literature on leadership styles by conducting a comprehensive bibliometric analysis of master’s and doctoral theses from the past three years (2022, 2023, and 2024) in Turkey, specifically within the YÖKTEZ database.This analysis aims to identify which sectors have been studied in relation to leadership styles in Turkish master's and doctoral theses, as well as the universities and academic disciplines that have focused on these styles. The study will also evaluate parameters such as the methodological approaches employed in these theses, the target audiences studied, and the sectors examined in the research. The objective is to provide a general profile of academic interest and trends in leadership and to offer a broader perspective on the current state of leadership research in Turkey.
Keywords: Leadership; Leadership Styles; Bibliometric Analysis; Academic Theses; Management